Near well-bore sealing in the Bečej CO2 reservoir: Field tests of a silicate based sealant. (April 2019) - Wiese, Bernd U.; Fleury, Marc; Basic, Ivan; Abdollahi, Jafar; Patrnogic, Aleksandar; Hofstee, Cor; Carlsen, Inge M.; Wollenweber, Jens; Schmidt-Hattenberger, Cornelia; Drysdale, Robert; Karas, Dusan
Highlights: Develop a gel to block gas movement in CO2 reservoirs. The gel is selectively reactive to CO2 . Design was focussed on field applicability. The formulation is flexible and can be modified for different conditions. The large scale of a sealing experiment is unique in the history of CO2 storage research. The European Storage Directive imposes a corrective measures plan as part of the license for demonstration-scale projects. Abstract: A silica gel was applied in a porous gas reservoir, with the purpose of testing mitigation and remediation of CO2 leakage from geological storage reservoirs. The gel has a high strength and a very low water-like viscosity, that extends its applicability to small pore diameters and low permeability media. The gel was prepared and applied on-site with oilfield equipment. Mixing was upscaled from laboratory- to field-scale, including one unsuccessful attempt. Environmental concerns and additional health and safety requirements were modest as the formulation was composed only of the non-toxic commercial silica-based product Betol K28 T, acetic acid and fresh water. A well was selected and prepared in the Bečej natural CO2 field in Serbia, the well and reservoir were prepared and the gel was placed into a 600 m deep CO2 - and CH4 -bearing sandstone layer. The reservoir was selectively sealed to the gas cap through a fast, CO2 -selective gelation, while the hydraulic pathways of the liquid-filled part of the reservoir remained open. In the regions where no CO2 was present the gelation reaction was slower and the kinetic was temperature-accelerated. A numerical model was used to simulate the impact of the pre-injection operational procedures and to quantify the impact on the temperature-dependent gelation time. The workflow aligns the needs of a research project with the interests and practical priorities of an operating company.